2018
DOI: 10.1080/11263504.2018.1441197
|View full text |Cite
|
Sign up to set email alerts
|

An updated checklist of the vascular flora alien to Italy

Abstract: ambientale, sapienza università di roma, roma, italy; f Dipartimento di scienze e tecnologie Biologiche ed ambientali, università del salento, lecce, italy; g istituto Beni culturali, regione emilia-romagna, Bologna, italy; h centro conservazione Biodiversità (ccB), Dipartimento di scienze della Vita e dell'ambiente (DisVa), università di cagliari, cagliari, italy; i scuola di Bioscienze e medicina Veterinaria, università di camerino, macerata, italy; j Dipartimento di scienze della Vita, università di modena … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
541
1
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 362 publications
(560 citation statements)
references
References 133 publications
14
541
1
4
Order By: Relevance
“…Chorotypes and life forms where inferred from Pignatti 21 and the status of alien species from Galasso et al . 22 . The dispersal methods of species were assigned followed the guidelines of van der Pijl 23 and Willson & Traveset 24 .…”
Section: Methodsmentioning
confidence: 99%
“…Chorotypes and life forms where inferred from Pignatti 21 and the status of alien species from Galasso et al . 22 . The dispersal methods of species were assigned followed the guidelines of van der Pijl 23 and Willson & Traveset 24 .…”
Section: Methodsmentioning
confidence: 99%
“…The percentage of alien species is very low (1.3%), compared with the percentage (12.8%) reported by Galasso et al (2018), probably due to the altitude of the collection sites (always above 900 m) and to the relative low rate of anthropization of the habitats explored. This low percentage reveals that the area includes environments with a high degree of wildness.…”
Section: Discussionmentioning
confidence: 49%
“…17% of the flora of Piemonte (4015 taxa, according to Bartolucci et al 2018 andGalasso et al 2018); they were found over an area that represents only 0.4% of the Regional area (the Crissolo, Oncino and Ostana municipalities occupy a surface area of 113 km 2 , out of the 25,387 km 2 of the total). Endemics (six) amount to almost 0.9% of the taxa observed and to 3.8% of the endemic species present in Piemonte (158, according to Bartolucci et al 2018).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations